2007
DOI: 10.2169/internalmedicine.46.6207
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Prosthetic Valve Endocarditis Caused by Staphylococcus aureus Colonizing Skin Lesions in Severe Atopic Dermatitis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…When it comes to concerns about resistance, antibiotics should be used only when clinical signs of infection are present, rather than to decolonize when the skin has not been affected 19 . Continual use of antibiotics in an attempt to clear S. aureus colonization in AD may eventually result in failure of these antibiotics in the setting of invasive infections, which are not uncommon in AD 10,11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to concerns about resistance, antibiotics should be used only when clinical signs of infection are present, rather than to decolonize when the skin has not been affected 19 . Continual use of antibiotics in an attempt to clear S. aureus colonization in AD may eventually result in failure of these antibiotics in the setting of invasive infections, which are not uncommon in AD 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover, the ability of S. aureus to be internalized by a variety of nonphagocytic host cells, including human keratinocytes, 9 may contribute to the development of persistent or chronic infections and may finally lead to deeper tissue infections or dissemination. 10,11 Gilani et al 12 reported that treatment with topical or oral antibiotics can temporarily reduce colonization and improve AD severity, but benefits are lost after 3 months. In recent years, antibiotic resistance has been recognized as a serious and growing problem in dermatological practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While dental procedure is recognized as the most common cause of PVE, other ordinary conditions, eg., acne vulgaris, which can cause systemic infection, are often overlooked [4]. Regarding this, Clayton et al, reported that skin infection is a risk factor for infective endocarditis [5].…”
Section: Discussionmentioning
confidence: 99%
“…First, the origin of S. aureus remains speculative. S. aureus is frequently located on the skin [2]; thus, the portal of entry for bacteremia is the dermis or less likely the teeth, lungs, or kidneys. No other portal of entry was visible or plausible on inspection or instrumental investigations.…”
mentioning
confidence: 99%